The Effectiveness Of The Production-Oriented Approach In Enhancing English Writing Achievement And Motivation Among Year 8 Students In China - Wang, Wenxuan (2024)
English writing is particularly crucial for students at the basic education level. This study aims to address the current issues of poor writing achievement and low writing motivation among Chinese eighth-grade students by employing a production-oriented approach (POA). The research design followed the Explanatory Sequential (QUAN-Qual) Design of the mixed-methods approach, which the qualitative findings were used to help explain and support the quantitative results. The quantitative study employed purposive sampling to conduct a quasi-experimental study with 80 students, including 40 students in the experimental group who participated in eight weeks of POA. In the qualitative study, five students from the experimental group volunteered to participate in semi-structured interviews. The quantitative results of the writing test and MANCOVA analyzes showed that the experimental groups were significantly different (p <.05) from that of the control group in terms of language, content, and structure. Additionally, the questionnaire and independent sample t-test analyzes revealed that the writing motivation was significantly different (p <.05) for both intrinsic and extrinsic motivation.